2011
DOI: 10.1001/archinternmed.2011.518
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Exposure and Quality of Life in Patients With Heart Failure

Abstract: Even low levels of SHS are associated with lower scores in several aspects of HRQOL. Physicians should advise patients with heart failure and their families to avoid SHS exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Old age is a strong independent predictor of death and morbidity in patients with structural heart disease. Therefore, old age is a major risk factor with poor cardiovascular outcome and reduced endogenous cardioprotection 5 . Both the incidence and the severity of atherosclerosis and cardiovascular disease increases with age.…”
Section: Introductionmentioning
confidence: 99%
“…Old age is a strong independent predictor of death and morbidity in patients with structural heart disease. Therefore, old age is a major risk factor with poor cardiovascular outcome and reduced endogenous cardioprotection 5 . Both the incidence and the severity of atherosclerosis and cardiovascular disease increases with age.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation may also play an important role in heart failure outcomes. 12 Physicians should advice patients with heart failure and their families to avoid exposure to SHS. Moreover, the implementation of smoke-free legislations was related to reductions in acute coronary event hospitalizations in most populations evaluated and it's reinforce the urgent need to enact and enforce smoke-free legislations that protect all citizens.…”
Section: Discussionmentioning
confidence: 99%
“…11 Other study also report that exposure to SHS in people with heart failure was associated with generally lower HRQoL scores in univariate analysis, with statistically and clinically significant reductions in 3 subscale scores: role physical, emotional well-being and role emotional. 12…”
Section: Secondhand Smoke and Hrqolmentioning
confidence: 99%
“…5 6 19 20 Studies that examined the association between SHS exposure and physical functioning were mostly restricted to patient samples with inconclusive findings. [21][22][23] To our best knowledge, only one study examined the association between SHS exposure and HRQoL in the Swiss general population, which showed that SHS was associated with a significant decrease in HRQoL scores with a dose-response relationship. 24 Hong Kong is the most economically developed city of China with the most stringent tobacco control policy including comprehensive smoke-free legislation, raising tobacco tax, banning tobacco advertisings and promotions, and providing smoking cessation services.…”
Section: Introductionmentioning
confidence: 99%